Serum calcium ions, ratio of calcium/ creatinine urine and bone mass density in perimenopausal and postmenopausal women - Harjo Mulyono, Riswan Hadi Kusuma Windarwati (Universitas Gadjah Mada, 2014)
Early diagnosis of osteoporosis is important to take early prevention and treatment. Dual energyX-ray absorbtiometry (DEXA) scan is gold standard diagnosis of osteoporosis. However, it ishigh technology and high cost. Biochemical marker using calcium could be developed for diagnosisof osteoporosis. The study was conducted to evaluate the correlation between serum calciumions level as well as urine calcium and urine creatinine (UCa/UCr) ratio and Bone Mineral Density(BMD) in perimenopausal and postmenopausal women. This was an observational study withcross-sectional design involving women aged 45-75 years who fulfilled the inclusion and exclusioncriteria. Bone Mineral Density was measured using DEXA method. Serum and urine calcium ionswere measured using ISE method, while serum and urine creatinine were determined using Jaffemethod. Ratio of UCa/UCr were then calculated. The correlation between serum calcium ions aswell as the ratio UCa/UCr and BMD of subjects were then analyzed. A total 63 subjects wereinvolved in this study consists of 21 normal subjects, 22 subjects with osteopenia and 20subjects with osteoporosis. Negative correlation between BMD and age (r=-0.591; p=0.001)and positive correlation between BMD and body mass index (BMI) (r=0.432; p=0.001) wereobserved. No correlation between serum calcium ions and BMD (r= -0.145; p=0.258), howevernegative correlation between UCa/UCr ratio and BMD (r=-0.310; p=0.013) were reported.Furthermore, no correlation was found between serum calcium ions and lumbar BMD (r=0.036;p=0.778), while negative correlation was found between UCa/UCr ratio and lumbar BMD (r= -0.414; p=0.001). In conclusion, there is no correlation between serum calcium ions levels andBMD, however there is a weak negative correlation between UCa/UCr ratio and BMD